2014
DOI: 10.1002/ajmg.a.36592
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing identifies compound heterozygous mutations in C12orf57 in two siblings with severe intellectual disability, hypoplasia of the corpus callosum, chorioretinal coloboma, and intractable seizures

Abstract: In patients with genetically heterogeneous disorders such as intellectual disability or epilepsy, exome sequencing is a powerful tool to elucidate the underlying genetic cause. Homozygous and compound heterozygous mutations in C12orf57 have recently been described to cause an autosomal recessive syndromic form of intellectual disability, including agenesis/hypoplasia of the corpus callosum, optic coloboma, and intractable seizures. Here, we report on two siblings from nonconsanguineous parents harboring two co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Although the structure and function of its product are not known, biallelic variants in C12orf57 have been identified in familial and sporadic cases of microphthalmia with bilateral iris and/or chorioretinal coloboma (Patel et al 2018;Platzer et al 2014;Zahrani et al 2013), unilateral iris or chorioretinal coloboma and posterior staphyloma (Salih et al 2013), and microcornea with corneal opacity and dense cataract (Salih et al 2013). Additional neurologic features have been observed, such as global developmental delay and epilepsy, corpus callosum anomalies and behavioral difficulties, consistent with Temtamy syndrome (MIM#218340).…”
Section: C12orf57 (Chromosome 12 Open Reading Frame 57)mentioning
confidence: 99%
“…Although the structure and function of its product are not known, biallelic variants in C12orf57 have been identified in familial and sporadic cases of microphthalmia with bilateral iris and/or chorioretinal coloboma (Patel et al 2018;Platzer et al 2014;Zahrani et al 2013), unilateral iris or chorioretinal coloboma and posterior staphyloma (Salih et al 2013), and microcornea with corneal opacity and dense cataract (Salih et al 2013). Additional neurologic features have been observed, such as global developmental delay and epilepsy, corpus callosum anomalies and behavioral difficulties, consistent with Temtamy syndrome (MIM#218340).…”
Section: C12orf57 (Chromosome 12 Open Reading Frame 57)mentioning
confidence: 99%
“…Temtamy syndrome is an extremely rare disorder, and only a limited number of studies have been conducted (1)(2)(3)(4)(5)(6)(7). The present study reports the first East Asian patient with a novel C12orf57 homozygous pathogenic variant; all other heterozygous carriers in the family were clinically healthy.…”
Section: Discussionmentioning
confidence: 68%
“…In 2013, pathogenic variants of C12orf57 were first reported to cause Temtamy syndrome (3,4). At the present time, only seven pathogenic variants have been illustrated (1)(2)(3)(4)(5)(6). Those of Middle Eastern descent are particularly susceptible to C12orf57 pathogenic variants, with 54/56 (96.4%) of all the reported patients from Middle Eastern countries, predominantly Saudi Arabia (3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Exome sequencing studies identified homozygous and compound heterozygous mutations in C12orf57 to cause an autosomal recessive syndromic form of intellectual disability with ACC. C12orf57 is a highly conserved gene and is required for the development of the human corpus callosum [Akizu et al, 2013;Platzer et al, 2014].…”
Section: Discussionmentioning
confidence: 99%